AmAT19, an acetyltransferase from Astragalus membranaceus, catalyses specific 6α-OH acetylation for tetracyclic triterpenes and steroids. Issue 33 (10th August 2021) - Wang, Linlin; Chen, Kuan; Wang, Zilong; Yi, Yang; Zhang, Meng; Hasan, Aobulikasimu; Kuang, Yi; Shaker, Sharpkate; Yu, Rong; Wang, Haotian; Liu, Haiyang; Ye, Min; et al.
Abstract : AmAT19 could catalyze the specific 6 α -OH acetylation of tetracyclic triterpenes and steroids to improve their inhibitory activity against 3CL pro of SARS-CoV-2. Abstract : Tetracyclic triterpenes and steroids are pharmacologically important molecules, and acetylation could improve their bioactivities. In this study, a highly regio- and stereo-specific acetyltransferase, AmAT19, was discovered from Astragalus membranaceus . AmAT19 could selectively catalyze the 6α-OH acetylation of four tetracyclic triterpenes and steroids. The strict selectivity is associated with different orientations of the 6 α / β -OH as indicated by molecular docking. Acetylated products 1a, 3a and 4a remarkably increased the inhibitory activity against the 3-chymotrypsin-like protease (3CL pro ) of SARS-CoV-2, compared to 1, 3, and 4 . AmAT19 could be a promising catalyst for specific 6 α -OH acetylation to expand the molecular diversity of triterpenes and steroids.